(3bjGS YHA GdEfaGb Ydi GdUMI Ydi eSJhi eYjTI GdCSQI h GdabQ eJYOO GdCHYGO (B/ s - (3ShRGf YHOGdQMef eMeO eMeOs; (3aGQhb JeGe TYjH (B: s; (3eMeO QVG CHhfGRd (B: s; (3eMeO fLjH YHOGdaJGM (B: s ((3GdbGgQI (B: s (3ShRGf YHOGdQMef eMeO eMeO (B: s, 2021)
(3Ydi GdQZe ef CgejI GdYdGbI Hjf GdEfaGb Ydi GdUMI h GdabQ; GdE GffG fhGLg bUhQG TOjOG ai CYWGAgG GdCgejI GdeWdhHI(B. (3abO MXi ehVhY GdabQ (B- (3HUaI YGeI (B- (3HGgJeGe GdYOjO ef GdHGMKjf ai eUQ; HjfeG fOQJ GdOQGSGJ GdJi JfGhdJ CKQ GdEfaGb Ydi GdUMI ai GdhbhY ai OGFQI GdabQ(B. (3Cf eDTQGJ GdabQ GdJbdjOjI GdJi JSJfO Edi GdEfaGb GdGSJgdGci Jbdd ef eSJhjGJ GdabQ GdMbjbI(B. (3MjK jLH NUe eOahYGJ GdUMI NGQL GdLjH ef EfaGb GdCSQI GdeYjTjI h JMOjO eG EPG cGfJ bGOQI Ydi JdHjI GMJjGLGJgG GdCSGSjI(B. (3MjK JYJHQ GdCSQI GdeYjTjI abjQI HSHH eOahYGJ GdUMI ef GdLjH YfOeG jchf GLeGdi EfaGbgG GdGSJgdGci JMJ NW GdabQ HYO OaY GdeOahYGJ GdUMjI eeG jYcS GdCKGQ GdGabGQjI ddeOahYGJ GdUMjI(B. (3h ef gfG XgQ eONdGf CSGSjGf jSJNOeGf ai eYXe GdCOHjGJ GdSGHbI dbjGS CKQ eOahYGJ (B:(3dQYGjI GdUMjI Ydi GSJgdGc GdCSQ GdeYjTjI(B. (3MjK jbOeGf ebGjjS dJYOjd bjGSGJ GdabQ HfGA Ydi eOahYGJ GdUMI NGQL GdLjH(B. (3jbhe cd efgeG Ydi acQI Cf eOahYGJ GdQYGjI GdUMjI jLH CdG JJLGhR MOG eYjfG(B. (3HMjK jQcR GdeONd GdChd Ydi ONd GdCSQI Ch EfaGbgG GdGSJgdGci MjK jeKd eOahYGJ GdUMI cfSHI ef GdONd (B"(3Ch GdGSJgdGc(B" (3EcS HGSJNOGe YJHGJ eNJdaI ef (B2.5% (3Edi (B15%: (3h JhUja eOahYGJ GdUMI HCfgG cGQKjI YfOeG JJLGhR MUI GdEfaGb GdUMi GdYJHI GdeMOOI eSHbG ef GdONd(B/ (3RO (B2003s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddHMhK GdEMUGFjI (B- (3bSe GdEMUGA GdMjhi h GdScGfis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdabQs; (3YHA GdEfaGbs; (3eSJhi eYjTI GdCSQIs